Market Day Program for Low Class: Improving Independent Character Education at Elementary School - Oktaviana Saputri; Sukartono (Jurnal Pendidikan dan Pengajaran, 2023)
One of the central issues currently being discussed in the world of education is character education. Character education is experiencing disorientation, the fading of Pancasila values, and the shifting of life values as a result of globalization. This means that character education needs to be instilled from an early age, especially in elementary schools, one of which is independent character education. The aims of this study are to analyze the implementation of strengthening independent character education through "market day" for low grade students in elementary schools. This research uses descriptive qualitative research with a phenomenological research design. The research methods used are observation, interviews, and documentation. The validity of the data using triangulation of sources and techniques. Data analysis techniques include data collection, data reduction, data presentation, inference and verification. The results showed that in the market day program there were 3 stages, namely planning by holding monthly meetings by the school to form a market day management team, the implementation stage starting from students preparing goods stands, selling merchandise to bookkeeping and the evaluation stage once a week to monitor the development of student independence. The study used 5 independent indicators including doing their own work, taking initiative, not giving up, self-confidence and self-satisfaction, all indicators were fulfilled and indicated that the market day program was successful in being able to strengthen the independent character education of low-grade elementary school students in the very good category.